PARTNERSHIP IS THE KEY TO SUCCESSFUL STAKEHOLDER COLLABORATION IN STRENGTHENING RESILIENCE COASTAL COMMUNITY - Manurung, Yanto; Maarif, Syamsul; Toruan, Tahan Samuel Lumban; Swastanto, Yoedhi (Department of Government, FISIP, Universitas Padjadjaran, 2022)
Stakeholder collaboration through community participation and other sectors is an important element of sustainability in regional development. One form of community participation that is increasingly popular is collaborative management with a good governance approach. The purpose of this study is to find out how partnership is the key to the success of stakeholder collaboration in strengthening the resilience of coastal communities. This research uses descriptive-explanative research with a qualitative approach. This study uses content analysis techniques and library research. The search focused on the literature published until 2022. The results in this study explain that coastal area management strategies and planning,gb777